Investigation of Hybrid Energy Harvesting Circuits Using Piezoelectric and Electromagnetic Mechanisms - Mat Ali, Noraini; Mustapha, Ain Atiqa; Kok, Swee Leong (2013)
In this paper, a performance energy harvester generator with different configuration is determined by observing the output power and voltage charging of each configuration. The configuration consists of 4 structures. The first structure consists of a single piezoelectric cantilever. The second structure consists of copper coil with approximately 1000 turns and four magnets are configured in opposite polarities at the end of the cantilever beam. The third and the last structures configure in parallel and series using the same piezoelectric and electromagnetic generator. All the structure is connected to the single rectifier and the same storage system. It was found that, power generation of single PZT can generate optimum output up to 27.56mWatt and 3.44V charging voltage.